PREVENTION OF TRADITION, REGULARITY OF POSITIVE RECEIVES, DELL’ARTE CANONICAL CODE REVALUATION. COMMANDARY TRANSFORMATION OF COMMEDIA CIVILE RUSTICALE INTO COMMEDIA DELL’ARTE (ITALIAN DRAMATURGY) - Babenko, Valeriia (Літературний процес: методологія, імена, тенденції, 2019)
The author of the article studies the peculiarities of comedy dell’arte, regularities of its poetic techniques. Particular attention is drawn to the style and genre of the dramatic works. The masks of dell’arte (mainly zan), having gone from the notion of a dual creature that is on the verge of a funny and terrible, profane and sacred («spirits and ghosts» of the cult of the crops of fertility, devils of the mysterious action), to the mask types of comedy del arte and further - masks-characters in the work of Goldoni, at the turn of the 19–20 centuries, turned into a symbol of the ancient theater, theater-balagan, the theater is extremely conditional and play, emphasizing the concept of «theatrical theater» in art. Mask dell’arte as the unity of the actor and the character actually ceased to exist, but it was in the traditions of this theater and its characters found inspiration for directors, poets, artists at the turn of the century. The main artistic means of comedy dell’arte are analyzed. The conducted research shows that the main aesthetic principles of commedia dell’arte are reduced to the aesthetic system, which contains three essential elements: firstly, the theater is kept by a professional actor, who completely gives himself to the theater; secondly, the influence of the theater is stronger because of the synthesis of arts: plastic, music, dance and words; and thirdly, the soul of the performance is an action. The methods used in the paper are mixed: close reading, historical data processing, analyses of interdisciplinary resources (literary gerontology, social gerontology, theatre studies). The innovative solution lies in the application of interdisciplinary approach to close reading of drama texts. The results can be practical for classes of Italian literature and study of culture, theatre. DOI: https://doi.org/10.28925/2412-2475.2019.1310